Style in the Print Media: Perspectives from the Editorials of a Ghanaian Newspaper - Abrafi Adjei, Amma (Namibian Journal for Research, Science and Technology, 2020)
The study employs linguistic stylistic analysis, specifically, Leech and Shorts’ (2007) stylistic categories to identify the stylistic features used predominantly in selected newspaper editorials. The corpus used is made up of thirty editorials which are randomly selected. It employs the qualitative research design to analyse selected texts. The analysis reveals that the editorial of the Daily Graphic abounds in the use of stylistic features through the use of lexical items. Among others, the study discusses that the editorial makes use of major lexical items such as nouns, adjectives, adverbs and verbs, with nouns dominating the lexical choices and adjectives, the least. It adds that the use of different linguistic and stylistic features in the packaging of information is motivated and purposeful, because the features help in the interpretation and meaning of the editorial. The analysis of lexical items has helped to provide an interpretation to the editorials in addition to showing the communicative relationship between author and reader. Pedagogically, the study is significant in the sense that it provides an avenue for students and teachers of language to observe how the appropriate selection of lexical items helps in text construction and meaning creation. The study recommends that stylistic features are helpful in the packaging and interpretation of texts (editorials included), therefore, language users: writers, teachers, students and other users of language, especially in ESL and EFL contexts, should be guided in authentic use of linguistic items in the packaging of information in the language classroom and in other contexts. This study makes a modest contribution to understanding the relationship between collective action and collective identity in CBNRM and similar institutions.